Organometallic polyphosphorus and -arsenic ligands as linkers between pre-assembled linear CuI fragments. Issue 14 (13th January 2015) - Fleischmann, Martin; Dütsch, Luis; Moussa, Mehdi Elsayed; Schindler, Andrea; Balázs, Gábor; Lescop, Christophe; Scheer, Manfred
Abstract : We present a simple route to multimetallic Cu I building blocks and their interaction with organometallic polyphosphorus and -arsenic linkers affording in novel polynuclear complexes or one-dimensional coordination polymers. Abstract : A simple and straightforward synthesis of a new linear trinuclear Cu I cluster with polyphosphine ligands is presented. The reaction of this pre-organized Cu3 precursor with E n ligand complexes (E = P, As; n = 2, 5) affords discrete complexes exhibiting end-on η 1 -coordination of the E2 ligands or one-dimensional coordination polymers featuring σ-1, 3-bridging E5 rings, respectively.